Fit for School Study protocol: early child growth, health behaviours, nutrition, cardiometabolic risk and developmental determinants of a child’s school readiness, a prospective cohort - Peter Szatmari; Mark S Tremblay; Peter Jüni; Christopher Allen; Julia Thompson; Kevin Thorpe; Douglas Campbell; Andreas Laupacis; Elise Mok; Catherine S Birken; Jessica A Omand; Kim M Nurse; et al. (BMJ Open)
Introduction School readiness is a multidimensional construct that includes cognitive, behavioural and emotional aspects of a child’s development. School readiness is strongly associated with a child’s future school success and well-being. The Early Development Instrument (EDI) is a reliable and valid teacher-completed tool for assessing school readiness in children at kindergarten age. A substantial knowledge gap exists in understanding how early child growth, health behaviours, nutrition, cardiometabolic risk and development impact school readiness. The primary objective was to determine if growth patterns, measured by body mass index trajectories in healthy children aged 0–5 years, are associated with school readiness at ages 4–6 years (kindergarten age). Secondary objectives were to determine if other health trajectories, including health behaviours, nutrition, cardiometabolic risk and development, are associated with school readiness at ages 4–6 years. This paper presents the Fit for School Study protocol.Methods and analysis This is an ongoing prospective cohort study. Parents of children enrolled in the The Applied Health Research Group for Kids (TARGet Kids!) practice-based research network are invited to participate in the Fit for School Study. Child growth, health behaviours, nutrition, cardiometabolic risk and development data are collected annually at health supervision visits and linked to EDI data collected by schools. The primary and secondary analyses will use a two-stage process: (1) latent class growth models will be used to first determine trajectory groups, and (2) generalised linear mixed models will be used to examine the relationship between exposures and EDI results.Ethics and dissemination The research ethics boards at The Hospital for Sick Children, Unity Health Toronto and McMaster University approved this study, and research ethics approval was obtained from each school board with a student participating in the study. The findings will be presented locally, nationally and internationally and will be published in peer-reviewed journals.Trial registration number NCT01869530.